Pluralism in Architecture - Al-Hangaweh, wahda shuker (Iraqi Journal of Architecture and Planning, 2009)
whenÂ studying the concepts that form arclLitecture through analyzing its results along the time, the tension of intellect betwr:en the spiritual and intellectual aspects arises. The human civilizations through the history was always attempting to alien between the spiritual and metaphysical research , and the pure scientific research considering the first as studying the mysterious pheno nena , while science deals with what is researchable subject to analysis which provides a concrete base for discussion , as it offers clear facts that coutd be experimente,l and tested , because science demands from human beings to deal with the universe and the facts of life and death rationally , whereas life proves everyday that not all tlLe genuine are realistic , and the interpretation stays the flame structure through whi ch we look at facts of life in the process of searching for the variable in the invariable , and for all invariable in the variables . The research includes an attempt to clarify the concept ofmonism and pluralism in the human intellect and the concept ol pluralism in the architectural work. The research has reached to explain the con,:ept ofpluralism in architecture through the changing of the intellectual concepts in p ost modern architecture against the concept of monism that modem architecture aC opted and their influence upon creativity in architectural work.